REPRESENTASI DAKWAH MAGIS (ANALISIS SEMIOTIKA DALAM YOUTUBE KANG UJANG BUSTHOMI CIREBON) - Lukman Al Farisi; Zidni Ilman Nafia; Moh Muslimin (Fakultas Usluhuddin dan Dakwah IAIN Kediri, 2021)
This study aims to describe the representation of the magical da'wah of Kang Ujang Busthomi Cirebon associated with the use of social media Youtube. The diversity of media used by da'i has also become a concern for researchers to re-examine the value of the effectiveness of the media as a medium of preaching. This study uses a qualitative approach using the semiotic analysis method of Roland Barthes. This method is used to read various signs and signs marking the magical da'wah of Ustad Ujang Busthomi which contains messages that are conveyed to viewers and subscribers. The results show that the representation of magical da'wah in various symbols refers to the battle of religious symbols and symbols of polytheism. This is shown through display symbols such as the use of magical objects, irrational and non-physical magical readings that are collaborated with religious rituals as seen in Islamic teachings. , , Magis, Youtube.